## Tìm số tự nhiên x , biết

Question

Tìm số tự nhiên x , biết

in progress 0
8 tháng 2020-10-17T15:44:33+00:00 1 Answers 76 views 0

1. Giải thích các bước giải:

$11/$ $240 : (x – 5) = 2^{2} . 5^{2} – 20$

$240 : (x – 5) = 4 . 25 – 20$

$240 : (x – 5) = 100 – 20$

$240 : (x – 5) = 80$

$x – 5 = 240 : 80$

$x – 5 = 3$

$x = 3 + 5$

$x = 8$

$Vậy$ $x = 8$

$12/$ $70 : (x – 3) = (3^{4} – 1) : 4 – 10$

$70 : (x – 3) = (81 – 1) : 4 – 10$

$70 : (x – 3) = 80 : 4 – 10$

$70 : (x – 3) = 20 – 10$

$70 : (x – 3) = 10$

$x – 3 = 70 : 10$

$x – 3 = 7$

$x = 7 + 3$

$x = 10$

$Vậy$ $x = 10$

$13/$ $75 : (x + 2) = 5^{3} – (3^{2} + 4^{2}) . 2^{2}$

$75 : (x + 2) = 125 – (9 + 16) . 4$

$75 : (x + 2) = 125 – 25 . 4$

$75 : (x + 2) = 125 – 100$

$75 : (x + 2) = 25$

$x + 2 = 75 : 25$

$x + 2 = 3$

$x = 3 – 2$

$x = 1$

$Vậy$ $x = 1$

$14/$ $260 : (x + 4) = 5 (2^{3} + 5) – 3 (3^{2} + 2^{2})$

$260 : (x + 4) = 5 (8 + 5) – 3 (9 + 4)$

$260 : (x + 4) = 5 . 13 – 3 . 13$

$260 : (x + 4) = (5 – 3) . 13$

$260 : (x + 4) = 2 . 13$

$260 : (x + 4) = 26$

$x + 4 = 260 : 26$

$x + 4 = 10$

$x = 10 – 4$

$x = 6$

$Vậy$ $x = 6$

$15/$ $(2^{2} + 3)(x – 5) + 14 = 5^{2} + 124 : 2^{2}$

$(4 + 3)(x – 5) + 14 = 25 + 124 : 4$

$7 (x – 5) + 14 = 25 + 31$

$7 (x – 5) + 14 = 56$

$7 (x – 5) = 56 – 14$

$7 (x – 5) = 42$

$x – 5 = 42 : 7$

$x – 5 = 6$

$x = 6 + 5$

$x = 11$

$Vậy$ $x = 11$

$16/$ $3^{2} (x + 1) – 3 = 2^{3} + (7^{2} . 2) : 14$

$9 (x + 1) – 3 = 8 + (49 . 2) : 14$

$9 (x + 1) – 3 = 8 + 98 : 14$

$9 (x + 1) – 3 = 8 + 7$

$9 (x + 1) – 3 = 15$

$9 (x + 1) = 15 + 3$

$9 (x + 1) = 18$

$x + 1 = 18 : 9$

$x + 1 = 2$

$x = 2 – 1$

$x = 1$

$Vậy$ $x = 1$

$17/$ $2^{2} . 3 (x + 5) – 6^{2} = (2^{3} + 2^{2}) . 2^{2}$

$4 . 3 (x + 5) – 36 = (8 + 4) . 4$

$4 . 3 (x + 5) – 36 = 12 . 4$

$4 . 3 (x + 5) – 36 = 48$

$4 . 3 (x + 5) = 48 + 36$

$4 . 3 (x + 5) = 84$

$3 (x + 5) = 84 : 4$

$3 (x + 5) = 21$

$x + 5 = 21 : 3$

$x + 5 = 7$

$x = 7 – 5$

$x = 2$

$Vậy$ $x = 2$

$18/$ $(2^{2} + 1)(x + 14) = 5^{2} . 4 + (2^{5} + 3^{2} + 7^{2}) : 2$

$(4 + 1)(x + 14) = 25 . 4 + (32 + 9 + 49) : 2$

$5 (x + 14) = 100 + (41 + 49) : 2$

$5 (x + 14) = 100 + 90 : 2$

$5 (x + 14) = 100 + 45$

$5 (x + 14) = 145$

$x + 14 = 145 : 5$

$x + 14 = 29$

$x = 29 – 14$

$x = 15$

$Vậy$ $x = 15$

$19/$ $(2^{2} – 1)(x – 1) = 2^{2} + (6^{2} + 2^{6}) : (5^{2} . 2)$

$(4 – 1)(x – 1) = 4 + (36 + 64) : (25 . 2)$

$3 (x – 1) = 4 + 100 : 50$

$3 (x – 1) = 4 + 2$

$3 (x – 1) = 6$

$x – 1 = 6 : 2$

$x – 1 = 3$

$x = 3 + 1$

$x = 4$

$Vậy$ $x = 4$

$20/$ $(3^{2} – 2)(x – 12) + 35 = 5^{2} + 279 : 3^{2}$

$(9 – 2)(x – 12) + 35 = 25 + 279 : 9$

$7 (x – 12) + 35 = 25 + 31$

$7 (x – 12) + 35 = 56$

$7 (x – 12) = 56 – 35$

$7 (x – 12) = 21$

$x – 12 = 21 : 7$

$x – 12 = 3$

$x = 3 + 12$

$x = 15$

$Vậy$ $x = 15$